Antioxidant Test and Flavonoids Determination of Tuber Pakis Kinca (Nephrolepis cordifolia (L) C. Presl) - Samsul Hadi; Arif Subekti; Amalia Khairunnisa (Indonesian Journal of Chemical Analysis (IJCA), 2023)
One of the things that causes cell damage in the body is the formation of unpaired electrons, also known as free radicals, which can cause oxidative stress. Excessive oxidative stress is not maintained by the body's natural antioxidants, so natural antioxidants are needed from outside. One of the plants suspected of having antioxidant abilities is Pakis kinca. So, the aim of this study was to determine the levels of flavonoids and antioxidant abilities in the tuber of N. cordifoli. Therefore, the method used to determine flavonoids is by reacting with AlCl3 and reading by UV-vis spectrophotometry, while reacting antioxidants with DPPH using spectrophotometry. The results of the flavonoid test were 3.119 ± 0.09 w/w equivalent to quercetin, from this equation the flavonoid content in the range of the equation was obtained. The results of the antioxidant test obtained the mean value of antioxidants was 93.898 ± 0.923. The conclusion obtained is that the antioxidant IC50 value of tuber extract N. cordifolia is a strong category with a total flavonoid content of 3.119 ± 0.091 w/w equivalent to quercetin.